2017
DOI: 10.1186/s40623-017-0668-5
|View full text |Cite
|
Sign up to set email alerts
|

Shear strain concentration mechanism in the lower crust below an intraplate strike-slip fault based on rheological laws of rocks

Abstract: We conduct a two-dimensional numerical experiment on the lower crust under an intraplate strike-slip fault based on laboratory-derived power-law rheologies considering the effects of grain size and water. To understand the effects of far-field loading and material properties on the deformation of the lower crust on a geological time scale, we assume steady fault sliding on the fault in the upper crust and ductile flow for the lower crust. To avoid the stress singularity, we introduce a yield threshold in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Results indicate that a combination of deformation in the upper crust as well as ductile deformation in the lower crust may contribute to the high strain rate in the northeastern NKTZ. Zhang and Sagiya (2017) modeled strain concentration in two dimensions within the lower crust, assuming steady fault sliding in the upper crust and ductile flow in the lower crust according to laboratoryderived power-law rheology with a yield threshold at the brittle-ductile transition. Possible physical mechanisms for strain concentration in the lower crust are investigated including frictional and shear heating, grain size, and power-law creep, taking account also of the role of water in promoting crystal plasticity.…”
mentioning
confidence: 99%
“…Results indicate that a combination of deformation in the upper crust as well as ductile deformation in the lower crust may contribute to the high strain rate in the northeastern NKTZ. Zhang and Sagiya (2017) modeled strain concentration in two dimensions within the lower crust, assuming steady fault sliding in the upper crust and ductile flow in the lower crust according to laboratoryderived power-law rheology with a yield threshold at the brittle-ductile transition. Possible physical mechanisms for strain concentration in the lower crust are investigated including frictional and shear heating, grain size, and power-law creep, taking account also of the role of water in promoting crystal plasticity.…”
mentioning
confidence: 99%
“…Water fugacity is calculated with the van der Waals equation (Karato, 2012). The detailed calculation method can be found in Zhang and Sagiya (2017).…”
Section: Rheologiesmentioning
confidence: 99%
“…Previous investigations of the deformation of the lower crust and the upper mantle using mechanical models have shown that localized shear deformation can be developed in the lower crust under the interplate (e.g., Allison & Dunham, 2018;Moore & Parsons, 2015;Takeuchi & Fialko, 2012;Thatcher & England, 1998) and intraplate (e.g., Zhang & Sagiya, 2017) strike-slip faults. Some of these models considered earthquake cycles (e.g., Allison & Dunham, 2018;Erickson et al, 2017;Lambert & Barbot, 2016;Takeuchi & Fialko, 2012) and others considered a creeping fault (e.g., Moore & Parsons, 2015;Thatcher & England, 1998;Zhang & Sagiya, 2017) in the upper crust. The localized deformation in the lower crust under a fault appears in all these models.…”
Section: Comparison With Mechanical Models For Interplate Strike-slipmentioning
confidence: 99%
See 2 more Smart Citations